2019
DOI: 10.1111/petr.13523
|View full text |Cite
|
Sign up to set email alerts
|

20‐ to 25‐year patient and graft survival following a single pediatric liver transplant—Analysis of the United Network of Organ Sharing database: Where to go from here

Abstract: To understand factors contributing to liver graft loss and patient death, we queried a national database designed to follow pediatric patients transplanted between 1987 and 1995 till adulthood. A comparison was made to a cohort transplanted between 2000 and 2014. The 5‐, 10‐, 15‐, 20‐, and 25‐year patient survival and graft survival were 95.5%, 93.7%, 89.1%, 80.8%, and 73.1%, and 92.5%, 86.7%, 77.6%, 68.7%, and 62.2%, respectively. The twenty‐year patient/graft survival was significantly worse in those transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…For example, while PELD and MELD scoring systems have led to a drastic decrease in mortality, it has been shown that their implementation has actually led to increased costs and that the score alone is not a perfect predictor of post‐transplantation complications 5‐8 . Meanwhile, other variables have been shown to be associated with complications following surgery and, in particular, the post‐transplant LOS in the hospital 9‐13 . Importantly, a longer stay in the hospital following a pediatric liver transplant has been directly associated with worse outcomes, more complications, and subsequently higher costs 14 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, while PELD and MELD scoring systems have led to a drastic decrease in mortality, it has been shown that their implementation has actually led to increased costs and that the score alone is not a perfect predictor of post‐transplantation complications 5‐8 . Meanwhile, other variables have been shown to be associated with complications following surgery and, in particular, the post‐transplant LOS in the hospital 9‐13 . Importantly, a longer stay in the hospital following a pediatric liver transplant has been directly associated with worse outcomes, more complications, and subsequently higher costs 14 .…”
Section: Introductionmentioning
confidence: 99%
“…This stands in contrast to most studies, which-if at all-have found early infancy to be a risk factor for impaired survival [6,8,11,25,26], or seen no influence at all [27]. One study found superior results for patient and graft survival in small infants [13], and two studies also found older patients at a higher risk of mortality [25,28]. The better outcome of infants in our center may be related to comparably longer experience in partial and split liver transplantation in our center, both in surgical and pediatric care.…”
Section: Recipient-specific Variables Influencing Patient Survivalmentioning
confidence: 72%
“…The analysis of factors influencing graft survival revealed a lower risk for graft loss in the group of patients between 6 and 12 years of age. As age groups have been defined differently, a direct comparison is difficult, but some other studies have seen this age group rather as a risk factor for an unfavorable outcome [18,28] and liver recipients in infancy at a higher risk of graft loss [30]-which we could not reproduce in our analysis.…”
Section: Recipient-specific Variables Influencing Graft Survivalmentioning
confidence: 91%
“…Women constitute 37% of patients who have had liver transplantation, with about 12% being of reproductive age (18‐49 years old). Another 5% are pediatric female liver transplant recipients, who have > 80% survival into adulthood and thus may likely consider pregnancy 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…5 Women constitute 37% of patients who have had liver transplantation, with about 12% being of reproductive age (18-49 years old).Another 5% are pediatric female liver transplant recipients, who have > 80% survival into adulthood and thus may likely consider pregnancy. 5,6 Since the first pregnancy in a liver transplant recipient in 1978, outcomes for both mother and fetus have greatly improved. Recent studies report a 20-year maternal survival rate of 53% and a live birth rate of 75% 7,8 in patients who became pregnant after liver transplantation.…”
mentioning
confidence: 99%